Effect of Replacing Sodium Nitrite with Celery on Sensory and Chemical Quality of Popular Dry Sausage - Rashad Mohammed Ali Alkazzaz, Sami; Abdellatif Abdelrahman, Hosny; Meawad Ahmed, Ali; Hassan Ibrahim Dora, EL-Desoky; Mahmoud Helal, Ihab; Ibrahim Hussein Ahmed, Nada (Journal of Advanced Veterinary Research, 2022)
The global economic crisis led to the tendency of consumers to search for cheap food sources of animal origin, including dry sausage, regardless of the quality or safety factor. Nitrite is an important meat additive responsible for the distinctive color and flavor of meat products, inhibits the development of microbial spores, and delays lipid oxidation. At the same time, it has adverse health risks for meat consumers. Celery, Apium graveolens, as a plant rich in nitrate was used in this study for replacing the synesthetic chemical nitrite used in sausage manufacture. Dry sausage samples were divided into three equal groups, the first group without adding sodium nitrite and kept as a control group. The second group was treated with 100 mg/kg of sodium nitrite while the third group was treated with 0.3% celery powder. All groups were periodically examined for sensory and chemical quality parameters. Generally, there are no significant differences (P>0.05) found between sausage groups attributes to appearance. The results of color, flavor, smell, nitrite content, TVN, and TBA of control sausage samples were statistically lower (P<0.05) than those of treated sausage groups. No differences (P>0.05) were found for the attribute color, flavor, smell, nitrite content, TVN, and TBA between those treated with 100 ppm sodium nitrite and 0.3% celery sausages groups. The obtained results concluded that safe dry sausage could be produced with high quality without the addition of synthetic sodium nitrite, by replacing it with 0.3% celery powder. Celery offers a high potential nitrite as natural substitutes improve both the sensory and chemical quality of the dry sausage. However, further research is needed to irrefutably determine all potential benefits content of the celery.